Factores personales y tipo de cáncer cervical en pacientes del Centro Oncológico Hospital Regional de Loreto Iquitos 2020 al 2022 - López Romero, Jackeline Stefany (2024)
The objective was to determine the relationship between personal factors such as age, Human Papillomavirus (HPV) vaccine, history of cancer, parity, abortions, sexual partners, initiation of sexual relations, smoking, use of contraceptives, sexually transmitted infections. (STI) and the type of cervical cancer, in patients treated at the Oncology Center of the Regional Hospital of Loreto, Iquitos from 2020 to 2022; quantitative study, descriptive, correlational and retrospective design, the sample consisted of 223 clinical records, the technique used was documentary review, the instrument was a data collection sheet. The hypothesis test used chi2 α ≤ 0.05. The results were: a significant statistical relationship between HPV vaccine (p=0.006), STI (p=0.017) with cervical cancer, however no statistically significant relationship was found between age (p=0.811), history (p= 0.465), parity (p=0.930), number of partners (p=0.444), initiation of sexual life (p=0.523), smoking (p=0.455), use of contraceptives (p=0.455 ), concluding: that personal factors such as the HPV and STI vaccine are statistically related to cervical cancer in patients treated at the Oncology Center of the Regional Hospital of Loreto, Iquitos 2020 – 2022.